2020
DOI: 10.1177/1120672120934983
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic binasal hemianopia: case report and literature review

Abstract: A 56-year-old lady was referred for complete binasal hemianopia noticed during routine glaucoma screening. On examination the patient was asymptomatic, there were no ophthalmic causes explaining her visual field defect and further neurologic investigation was normal. Binasal hemianopia is an uncommon finding that is usually associated to intraocular conditions, but may rarely be caused by neurologic diseases. The Authors also review the current ophthalmic literature about binasal hemianopia in patients with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Detailed consideration of the case presents a series of reasons to regard the automated visual field report with skepticism: 1. The automated visual field suggests a binasal hemianopia, an uncommon abnormality most often a result of such bilateral ocular diseases as optic nerve pathologies -ischemic optic neuropathy, optic nerve head drusen, glaucoma, bilateral optic nerve pits, papilledema, or optic atrophy [1,2]. Retinal diseases, including retinitis pigmentosa sine pigmento [1] or corneal pathology as keratoconus [3], have also described as possible causes of binasal defect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed consideration of the case presents a series of reasons to regard the automated visual field report with skepticism: 1. The automated visual field suggests a binasal hemianopia, an uncommon abnormality most often a result of such bilateral ocular diseases as optic nerve pathologies -ischemic optic neuropathy, optic nerve head drusen, glaucoma, bilateral optic nerve pits, papilledema, or optic atrophy [1,2]. Retinal diseases, including retinitis pigmentosa sine pigmento [1] or corneal pathology as keratoconus [3], have also described as possible causes of binasal defect.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal diseases, including retinitis pigmentosa sine pigmento [1] or corneal pathology as keratoconus [3], have also described as possible causes of binasal defect. In rare cases, binasal hemianopia has been attributed to neurological etiologies, including bilateral internal carotid artery aneurysms or atherosclerosis [4], hydrocephalus [5], olfactory groove meningioma [5], intracranial mass lesions, and pituitary apoplexy [1]. Pringle et al [6] reported a case of progressive binasal visual field loss due to neurosyphilis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying causes of BNH can be classified into three categories according to the anatomical location, (i) ocular lesions, such as keratoconus, glaucoma, drusen, and retinitis pigmentosa, (ii) optic nerve lesions including optic chiasm, such as syphilitic ON, ischemic optic neuropathy, internal carotid artery aneurysm and atherosclerosis, pituitary apoplexy, pneumosinus dilatans, and olfactory groove meningioma, (iii) intracranial lesions, such as brain tumor, the elevation of intracranial pressure, and occipital lobe lesions [ 6 , 7 ]. Salinas-Garcia et al reported in 75% of cases with BNH originate from ocular lesions or optic nerve [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike homonymous and bitemporal hemianopia, BNH is a rarely encountered neuro-ophthalmological finding. Since visual signals from the nasal visual fields do not cross but pass through the lateral nerve fibers at the optic chiasm, bilateral temporal optic nerve fiber lesions or uncrossed optic nerve fibers should be considered as responsible lesions of BNH [ 6 , 7 ]. Here, we describe a case of BNH secondary to bilateral OPN presumably caused by sarcoidosis, which to our knowledge, is the first such report in the literature.…”
mentioning
confidence: 99%